European Romanticism - Halmi, NA (Cambridge University Press, 2019)
Attempts to define Romanticism characteristically begin by conceding the difficulty, even impossibility, of the task. The entry on the subject in an encyclopedia of German literary history summarizes the challenge: “The Romantic movement must be understood as a unity, but it is in itself so polymorphous and contradictory that both a definition and an historical presentation are extraordinarily difficult.” Rather than proposing a normative definition, as if that were possible, this chapter will take the resistance to definition and its historical roots as keys to understanding Romanticism as distinctly European and modern. Accordingly, the focus here will be less on the art produced during the early decades of the nineteenth century, when Romanticism began to be theorized as a contemporary concern, than on discursive self-understanding in that unsettled period in which, as the poet William Wordsworth acknowledged, “a shock had then been given / To old opinions; and the minds of all men / Had felt it.”